A Prospective Study on Morphologic Pattern of Adverse Cutaneous Eruption of Co-trimoxazole among The Industrial Worker of Dhaka EPZ Area, Bangladesh (Journal of Current and Advance Medical Research, 2025)
Background: Drug reaction of Co-trimoxazole or Trimethoprim and Sulphamethoxazole (TMP-SMX) vary in their appearance and severity. They can range from simple pruritus or rash to severe life-threatening condition and even death.Objective: The objective of this study was to observe the morphologic pattern of adverse cutaneous eruption of co-trimoxazole among industrial workers.Methodology: This prospective observational study was conducted in department of Dermatology & Venereology, Monno Medical College, Manikganj, Bangladesh from January 2022 to December 2022 for a period of one year. This study was carried out on diagnosed cases of drug eruption after use of co-trimoxazole in DEPZ hospital in an industrial area of savar, Dhaka, Bangladesh. Adverse reactions to Co-trimoxazole were found in 44 patients with various morphology.Results: In this study majority patients were found in age group 20 to 30 years which were 28 (63.63%) followed by 31 to 40 years which were 10(22.72%) and 41 to 50 years which were 6(13.63%). Male were predominant than female which are 37(84.09%) and 07 (15.90%) respectively. The majority were labelled as fixed drug eruption in case of male 22 (50.00%) and female 03 (6.81%),and urticarial rash in case of male 5 (11.36%) and female 02 (4.54%). Others presentation with maculo-popular rash i in case of male 05(11.36%) and female 01 (2.27%). bullous eruption in case of male 05 (11.36%) and female 01 (2.27%).Conclusion: Adverse drug reactions are common complications in drug therapy. From this study it was observed, that Cotrimoxazole was a major etiological agent in causing cutaneous eruption.Journal of Current and Advance Medical Research, January 2024;11(1):17-21